The Transmission Mechanism in Armenia : New Evidence from a Regime Switching VAR Analysis. (IMF Working Papers; Working Paper ;, 2010)
The introduction of inflation targeting in 2006, together with important economic developments such as dedollarization, marked the beginning of a new macroeconomic framework in Armenia, which is likely to have changed the effectiveness of monetary policy. This paper is the first attempt to analyze whether the transmission mechanism in Armenia has been subject to a structural break by employing a Markov-Switching VAR framework. Results support the existence of such a structural break around the time inflation targeting was introduced and reduced levels of dollarization were observed. Results from introducing a threshold variable into this framework furthermore show that reduced levels of dollarization are an important determinant of the effectiveness of monetary policy.